Simulation and visualisation of perching manoeuvres - Goo, Yik Wen. (2011)
The application of the avian perching manoeuvre in man-made aircraft is an area of active research today. Currently, the majority of the research being done in this field is in the form of simulation and analysis using theoretical methods, while other researchers focus on the latching mechanism for use in perching. Notably, there is no exploration of the usage of flight simulation software capable of real-time visualisation and manual control of an aircraft in perching. This project describes the process and results of using flight simulation software known as SimGen and DSix for the modelling and flight simulation of a perching UAV. A 3D model of a UAV was created in SimGen using its 3-view drawing while perching was simulated in DSix using the aerodynamic data of the UAV predicted by SimGen. Results of perching under various conditions including step and ramp control deflection inputs, modified lift and pitching moment curves, etc. DSix was able to simulate and visualise perching effectively. Simulation results from DSix were plotted and shown to be physically meaningful. The accuracy of the simulation can be further improved with experimental aerodynamics data if necessary. Nevertheless, the versatility of DSix in accepting various modifications to the perching simulation was useful in finding the trends arising from different perching conditions. Visualisation of the manoeuvre provided visual verification of a successful perching manoeuvre, while at the same time allowing the user to see any problems in the manoeuvre that may not be evident from the plotted results.